Data from: Demographic histories and genetic diversities of Fennoscandian marine and landlocked ringed seal subspecies - Nyman, Tommi; Valtonen, Mia; Aspi, Jouni; Ruokonen, Minna; Kunnasranta, Mervi; Palo, Jukka U. (Zenodo, 2015)
Island populations are on average smaller, genetically less diverse, and at a higher risk to go extinct than mainland populations. Low genetic diversity may elevate extinction probability, but the genetic component of the risk can be affected by the mode of diversity loss, which, in turn, is connected to the demographic history of the population. Here, we examined the history of genetic erosion in three Fennoscandian ringed seal subspecies, of which one inhabits the Baltic Sea 'mainland' and two the 'aquatic islands' composed of Lake Saimaa in Finland and Lake Ladoga in Russia. Both lakes were colonized by marine seals after their formation c. 9500 years ago, but Lake Ladoga is larger and more contiguous than Lake Saimaa. All three populations suffered dramatic declines during the 20th century, but the bottleneck was particularly severe in Lake Saimaa. Data from 17 microsatellite loci and mitochondrial control-region sequences show that Saimaa ringed seals have lost most of the genetic diversity present in their Baltic ancestors, while the Ladoga population has experienced only minor reductions. Using Approximate Bayesian computing analyses, we show that the genetic uniformity of the Saimaa subspecies derives from an extended founder event and subsequent slow erosion, rather than from the recent bottleneck. This suggests that the population has persisted for nearly 10,000 years despite having low genetic variation. The relatively high diversity of the Ladoga population appears to result from a high number of initial colonizers and a high post-colonization population size, but possibly also by a shorter isolation period and/or occasional gene flow from the Baltic Sea. Nyman_etal_to_DRYAD Text-formatted DIYABC data file containing microsatellite genotypes and mitochondrial control-region sequences of Saimaa, Ladoga, and Baltic ringed seals. Nyman_etal_to_DRYAD_reftableHeaders Text-formatted reftableHeader file containing scenarios, priors, and summary statistics used in the main DIYABC analyses